Determination of Gallon Mineral Water Distribution Route at PT. XYZ Using Capacitated Vehicle Routing Problem (CVRP) - Az-Zahra Nayak, Rifka Dahayu; Prihadianto, Rahaditya Dimas; Istiqomah, Silvi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT XYZ is experiencing problems, one of which is in the high cost of distribution because there is no special calculation in determining the route. The implementation of the distribution process carried out by PT XYZ is still ineffective and disorganized. The goal of this study is to determine the optimal distribution route design and provide improvements or input to PT XYZ in the process of distributing goods with minimum transportation costs. Solving the route problem at PT XYZ using the Capacitated Vehicle Routing Problem method with the python programming language through the VRPY package by considering factors such as distance and truck capacity. In the first conditions, there were 24 deliveries with a total cost of IDR 2,484,975 and 11 vehicles. After using the Capacitated Vehicle Routing Problem method, there are 23 deliveries with a total cost of IDR 2,380,000 and 8 vehicles, showing a decrease in distance of 115.7 km or 4%.